AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI SIRSAK (Annona muricata L.) TERHADAP PERTUMBUHAN BAKTERI Staphyllococcus haemolyticus - Marcelino Edo Ba Beang; Muh. Taufiqurrahman; Risny Oklyan (Jurnal Farmasi Etam (JFE), 2025)
Soursop is a plant that grows in tropical areas and has long been widely used as a traditional medicine for various diseases such as cystitis, diabetes, headaches, flu, asthma, and insomnia. The use of soursop seeds is still limited because they are usually thrown away Soursop seeds have almost the same phytochemical content as the leaves, it was found that 96% ethanol extract of soursop seeds positively contained alkaloids, flavonoids, saponins, steroids, terpenoids, and polyphenols. This study aims to determine the activity of ethanol extract of soursop seeds on the growth of Staphylococcus haemolyticus bacteria in vitro using the disc diffusion method with concentrations of 10%, 20 and 30%. The disc diffusion method measures the area of ​​the clear zone formed around a paper disc, used to determine antimicrobial activity. The results showed that the ethanol extract of soursop seeds (Annona muricata L.) has antibacterial activity against the growth of Staphylococcus haemolyticus bacteria at concentrations of 10%, 20%, and 30%. The average diameter of the inhibition zone for the ethanol extract of soursop seeds (Annona muricata L.) at concentrations of 10% (2,798 mm), 20% (4,392 mm), and 30% (5,741 mm), and the average for the positive control was 7.465 with a standard deviation of 2.49, categorized as very strong.